2021
DOI: 10.1177/09673911211052730
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic and mechanical properties of CNT-reinforced polymer-based hybrid composite materials using hygrothermal creep

Abstract: In the present work, a combination of experimental and numerical procedure is proposed to study the effects of different hygrothermal conditions on the creep strain, viscoelastic properties of nanocomposites, and mechanical properties of such nanocomposite-based carbon fiber–reinforced polymer (CFRP) hybrid composite materials. Ultrasonic probe sonicator is used to randomly disperse the multiwalled carbon nanotubes into an epoxy to minimize agglomerations. Dynamic mechanical analysis is employed to conduct the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…CNTs are promising candidates for reinforcing various polymers as they have remarkable mechanical strength, rigidity, and electrical conductivity. Incorporated into polymers, CNTs transfer their properties to the fabricated materials, yielding durable and lightweight nanocomposites [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs are promising candidates for reinforcing various polymers as they have remarkable mechanical strength, rigidity, and electrical conductivity. Incorporated into polymers, CNTs transfer their properties to the fabricated materials, yielding durable and lightweight nanocomposites [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that nanotubes improved the mechanical properties of polymer panels, reducing their weight [6] and increasing the efficiency of products based on epoxy resins [7]. In experimentation and theoretical research [8], the authors described carbon fiber plastic modification with carbon nanotubes. Paper [9] was devoted to enhancing the strength properties of polymers by testing the wear resistance of a sponge structure comprised epoxy resin and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%